2020
DOI: 10.2147/ijn.s247692
|View full text |Cite
|
Sign up to set email alerts
|

<p>Virucidal Action Against Avian Influenza H5N1 Virus and Immunomodulatory Effects of Nanoformulations Consisting of Mesoporous Silica Nanoparticles Loaded with Natural Prodrugs</p>

Abstract: Background: Combating infectious diseases caused by influenza virus is a major challenge due to its resistance to available drugs and vaccines, side effects, and cost of treatment. Nanomedicines are being developed to allow targeted delivery of drugs to attack specific cells or viruses. Materials and Methods: In this study, mesoporous silica nanoparticles (MSNs) functionalized with amino groups and loaded with natural prodrugs of shikimic acid (SH), quercetin (QR) or both were explored as a novel antiviral nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 105 publications
(138 reference statements)
2
21
0
Order By: Relevance
“…Briefly, these data showed significant inhibition exerted by nanoformulations compared to standard diclofenac drug or free Ru and/or Pip. The findings are in accordance with our previous data showing a notable anti-inflammatory influence in an induced versus free-form rat model for nanoformulation-based mesoporous silica nanoparticles for the flavonoid quercetin and shikimic acid (AbouAitah et al, 2020b ). Other studies also have reported this effect in animal tests (Xu et al, 2011 ; Rachmawati et al, 2016 ; de Almeida et al, 2018 ), showing the importance of nanoformulation delivery compared to the traditional methods of delivering anti-inflammatory drugs.…”
Section: Resultssupporting
confidence: 93%
“…Briefly, these data showed significant inhibition exerted by nanoformulations compared to standard diclofenac drug or free Ru and/or Pip. The findings are in accordance with our previous data showing a notable anti-inflammatory influence in an induced versus free-form rat model for nanoformulation-based mesoporous silica nanoparticles for the flavonoid quercetin and shikimic acid (AbouAitah et al, 2020b ). Other studies also have reported this effect in animal tests (Xu et al, 2011 ; Rachmawati et al, 2016 ; de Almeida et al, 2018 ), showing the importance of nanoformulation delivery compared to the traditional methods of delivering anti-inflammatory drugs.…”
Section: Resultssupporting
confidence: 93%
“…nitric acid was performed to obtain 2,6,14-trinitrootriptycene and 2,7,14-trinitrotriptycene constitutional isomers that successfully separated by column chromatography. Next, reduction 2,6,14-trinitrootriptycene was achieved using Pd/C in ethanol under refluxing, in order to obtain 2,6,14-triaminotriptycene (9), as shown in Scheme 1. The ZnO NPs were functionalized with TRP in a multi-step process:…”
Section: Triptycene Functionalizationmentioning
confidence: 99%
“…The maximum size distribution was recorded for ELG loaded NPs in ZnO NPs-NH 2 -COOH-TRP-ELG, with a mean size of 322. nm ± 23.8 nm (Figure 4D). Thus, the particle size distribution is modulated by different parameters, such as surface functionalization and drug loading [9,41].…”
Section: Particle Size Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mesoporous silica nanoparticles can attach on their surface active species to create antiviral agents against herpes simplex viruses (HSV) [35] . Other recent examples involving mesoporous silicas deal with rubella virus (RV) [36] and mumps virus, [37] and with diagnosis and production of antiviral drugs against avian influence H5 N1 virus [38] …”
Section: Barriers For Virusesmentioning
confidence: 99%